Metastatic colon involvement from primary adrenal gland angiosarcoma: a case report - Sarra Ben Rejeb; Safia Sakly; Rym Bahloul; Taieb Jomni; Kalthoum Dridi (Journal of Medical Case Reports)
Abstract Introduction Angiosarcoma is a rare and aggressive malignancy accounting for 1–2% of soft tissue sarcomas. Primary adrenal angiosarcomas are exceptionally rare, with fewer than 60 cases reported.To our knowledge, this is the first documented case of an adrenal angiosarcoma presenting as a colonic metastasis. Case report A 68-year-old Caucasian North African woman with a history of adrenalectomy for a right adrenal tumor presented with gastrointestinal bleeding, and endoscopy revealed a hemorrhagic ulcerative lesion in the sigmoid colon. Histopathological examination revealed a malignant vascular tumor. Immunohistochemistry showed positivity for CD31, erythroblastosis virus E26 transforming sequence related gene, and pan-cytokeratin, consistent with angiosarcoma. In light of her history, a review of the adrenalectomy specimen confirmed the diagnosis of primary adrenal angiosarcoma. Conclusion This case underscores the necessity of thorough pathological evaluation, use of vascular markers, and interdisciplinary collaboration to improve diagnosis and management.